Bentuk dan Tindak Tutur Direktif Guru Pembelajaran Bahasa Indonesia Kelas VIIE Di SMPN 9 Kota Kupang Tahun Pelajaran 2024/2025 - Gai, Niken Eka Putri; Djuli, Labu; Margareta, Karus M (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2025)
The purpose of this study was to describe the form and function of teacher's directive speech acts in Indonesian language learning class VII E at SMP N 9 Kupang City. The research subject subjected to the action was VII E at SMP N 9 Kupang City. The research approach used in this study is a qualitative approach that is descriptive in nature to collect data on language use, especially the language of Indonesian teachers' directive speech in Indonesian language learning inclass VII E of SMPN 9 Kupang City. Data collection techniques use observation, interview, and documentation techniques to observe directly, interview sources and document the data collected. data analysis techniques are carried out with qualitative description techniques. The results of the research obtained about the Forms and Functions of Teachers' Directive Speech Acts in Class VIII Indonesian Language Learning at SMPN 09 Lebong Tengah in the 2024/2025 academic year, the following conclusions were obtained. First, the form of directive speech acts includes 6 speech acts. The directive speech acts are command, request, invitation, advice, criticism, and prohibition. The forms of the six directive speech acts are almost all used by Indonesian language teachers when teaching class VIII at SMPN 9 Kupang City, but during the learning process from the beginning to the end, the speech acts most often used by Indonesian language teachers in class VIII are directive speech acts of orders, requests, and directive speech acts of invitation. Second, the functions of directive speech acts found in Indonesian language learning class VIII at SMPN 9 Kupang City are 21 functions of directive speech acts. The functions of directive speech acts found in this study include: 8 functions of directive speech acts of command, 4 functions of speech acts of request, 1 function of speech acts of invitation, 2 functions of directive speech acts of advice, 2 functions of directive speech acts of criticism, and 2 functions of speech acts of prohibition